Pengaruh Return on Asset, Total Assets Turnover, Price Earning Ratio dan Dividend Per Share Terhadap Harga Saham (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Pertambangan yang Terdaftar di BEI Periode 2015-2019 - Tamara Irna Sari; Isbandini Veterina (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2021)
This study aims to see the effect of the effect of Return on Asset (ROA), Total Asset Turn Over (TATO), Price Earning Ratio (PER), and Dividend Per Share (DPS) on share prices in mining sub-sector companies on the Indonesia Stock Exchange for the period of year. 2015-2019 and using a sample of 17 companies that match the criteria. Model data analysis and hypothesis testing using descriptive statistics, classical assumption test, multiple linear test. The test used the Microsoft Excel 2016 software assisted hypothesis, and the Statistical Package for Social Sciences (SPSS) version 23.0. The sampling technique used purposive sampling. The results prove that partially and simultaneously, Return on Asset (ROA), Total Asset Turn Over (TATO), Price Earning Ratio (PER), and Dividend Per Share (DPS) have a significant effect on stock prices.